Just Play Cognitive Modern Board and Card Games, It’s Going to Be Good for Your Executive Functions: A Randomized Controlled Trial with Children at Risk of Social Exclusion - Jorge Moya-Higueras; Marina Solé-Puiggené; Nuria Vita-Barrull; Verónica Estrada-Plana; Núria Guzmán; Sara Arias; Xesca Garcia; Rosa Ayesa-Arriola; Jaume March-Llanes (Children, 2023)
Modern board and card games are usually used for leisure. Few studies have focused on the type of game played in vulnerable populations. Therefore, the main aim of this study was to test the effectiveness of playing modern board and card games to enhance updating, inhibition, and flexibility in children at risk of social exclusion using games that activated specific basic executive functions. We developed a quadruple-blind randomized clinical trial during the COVID-19 pandemic. Sixty-eight participants (7–12 years old) were divided into two experimental groups: 35 children played games that directly activated basic executive functions, and 33 played games that directly triggered other cognitive domains. The primary statistical analysis consisted of mixed models. We found significant time effects in cognitive flexibility and inhibition and, to a lesser extent, in working memory in both gaming groups. We analyzed the cognitive profile of the games and found that all the games activated basic executive functions significantly, irrespective of the experimental group. Therefore, it is possible that playing any type of modern board and card game (excluding games with a high incidence of luck) could be beneficial for children at risk of social exclusion.